2018
DOI: 10.2147/clep.s154409
|View full text |Cite
|
Sign up to set email alerts
|

Predicting surgical intervention in patients presenting with carpal tunnel syndrome in primary care

Abstract: PurposeCarpal tunnel syndrome (CTS) is a symptomatic compression neuropathy of the median nerve. This study investigated the value of candidate prognostic factors (PFs) in predicting carpal tunnel release surgery.Patients and methodsThis is a retrospective cohort study set in the Clinical Practice Research Datalink. Patients ≥18 years presenting with an incident episode of CTS were identified between 1989 and 2013. Candidate PF’s defined in coded electronic patient records were identified following literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…However, in our analysis of recent data, the peak surgical rate was observed at or above 70 years. This implies that CTS patients with more severe symptoms get surgery irrespective of age, which is in line with other recent studies 24 , 25 . With regard to residential area, patients in rural areas received more CTR than those in the capital region, which might be related to their occupations, such as agriculture which is strenuous on wrist.…”
Section: Discussionsupporting
confidence: 92%
“…However, in our analysis of recent data, the peak surgical rate was observed at or above 70 years. This implies that CTS patients with more severe symptoms get surgery irrespective of age, which is in line with other recent studies 24 , 25 . With regard to residential area, patients in rural areas received more CTR than those in the capital region, which might be related to their occupations, such as agriculture which is strenuous on wrist.…”
Section: Discussionsupporting
confidence: 92%
“…11 Although studies have been done in the UK to capture the rate of carpal tunnel syndrome and decompression surgery, to date we have not found a study that reports complication rates including reoperation and other rarer complications in a general population. 2,5,13 We found that fewer men than women undergo primary carpal tunnel decompression, but they have an increased incidence of reoperation and serious local complications. There could be a variety of reasons for this increased incidence, but we postulate that it could be because of surgery being more technically difficult in a larger hand as there is a greater amount of subcutaneous tissue in the operative field, reducing surgical exposure of the transverse carpal ligament.…”
Section: Discussionmentioning
confidence: 97%
“… 11 Although studies have been done in the UK to capture the rate of carpal tunnel syndrome and decompression surgery, to date we have not found a study that reports complication rates including reoperation and other rarer complications in a general population. 2 , 5 , 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations